Intoxicated But Not Incapacitated: Are There Effective Methods to Assist Juries in Interpreting Evidence of Voluntary Complainant Intoxication in Cases of Rape? - Nitschke, Faye T. (Journal of interpersonal violence, 2021)
Jurors often negatively evaluate complainants making allegations of rape when those complainants were intoxicated at the time of the assault. It is, therefore, essential that legal practitioners have effective methods of ensuring that jurors use evidence of intoxication for the legally permissible purpose, which is to determine the complainant’s cognitive capacity to consent. This study examines whether providing judicial instructions about how jurors should make use of complainant intoxication evidence assists jurors to use this evidence appropriately. University students (N = 212) read a case synopsis of an Australian criminal trial in which the complainant described experiencing mild or moderate levels of cognitive impairment due to alcohol consumption. Participants were then given a standard instruction about using the evidence of the complainant’s intoxication or one that provided an upper decision limit for determining complainant cognitive capacity (providing inference support). As expected, presenting evidence about the complainant’s alcohol-impaired cognitive state attenuated participants’ negative perceptions of the complainant. The judicial instructions also assisted participants as they evaluated a moderately intoxicated complainant as less capable of consenting when participants received an instruction that supported the correct inference to draw from the evidence compared to a standard instruction. However, parallel mediation analysis showed that rape schemas mediated the relationship between perceived complainant capacity to consent and perceptions of defendant guilt. Judicial instructions that support perceivers’ inferences may assist participants to more appropriately evaluate information about complainants’ intoxication, however problematically, rape schemas still influenced decisions about defendant guilt.